Articulating Postmemory in Soledad Puértolas’s Música de ópera (ex æquo, 2023)
The study of representations of war beyond places of combat opens a space to consider the effects of that war on the society in conflict. Evocations of war linger through time and become articulated through the lens of postmemory, which for Marianne Hirsch (2012, 8) is “distinguished from memory by generational distance and from history by deep personal connection”. The literary representations of life off the battleground point to a social fabric that illuminates intergenerational relationships surrounding the Spanish Civil War (1936- 1939) and its aftermath, when society was divided across an ideological continuum. In Soledad Puértolas’s Música de ópera (2019), three generations of women come to terms with the effects of the Civil War on their family.
Keywords: postmemory, Spanish Civil War, trauma, testimony; Postmemory; Spanish Civil War; trauma; testimony